Fundamentals of criminal protection of the environment - Mariana Noelia Solari Merlo (Ius Humani. Jornal do direito, 2023)
Half a century has passed since the First Conference on the Environment was held within the United Nations. Since then, the legal protection of the planet has improved considerably on the regulatory level, without these advances being seen on the material level. Among the various legal instruments to be used, the recourse to criminal law, inconceivable at first, has become a necessity given the relevance of the interests exposed. In this sense, the present work analyzes the way in which this international recognition of the environment has been developed to the point of being considered, at present, a legal interest of an autonomous nature and with sufficient entity to justify the intervention of criminal law. Likewise, the transfer of these interests to the Spanish criminal legal field and the way in which they have been incorporated into the Criminal Code will be analyzed